Pemasaran Digital untuk Peningkatan Laba dan Branding UMKM - Artiwi, Nila Prasetyo; Denny Putri Hapsari, Denny Putri; Winasis, Persis Haryo; Muadudin, Muadudin; Mulyawati, Mulyawati (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2024)
The digital marketing engagement strategy was implemented to increase profits and branding of Micro, Small and Medium Enterprises (MSMEs) in Harundang Village, Cikeusal District, Serang Regency, Banten Province. Harundang Village has MSME potential in the form of opak, ceplis and papaya stick production. This Seminar activity on Digital Marketing aims to provide knowledge and open the community's insight into MSME players in optimizing the use of digital media as an effective marketing tool, so that they can expand market reach, increase interaction with consumers, and build a stronger brand image. Through collaboration between students and the Harundang Village community, this activity was carried out using the lecture method and various training and mentoring programs were implemented, including the use of social media, creative content strategies, and data analysis to understand consumer behavior. It is hoped that the results of implementing this strategy will show a significant increase in consumer engagement, sales growth, and strengthening MSME branding which will have an impact on improving the economy of the Harundang Village community. This article concludes that proper digital marketing engagement can be one of the keys to success for MSMEs in increasing competitiveness and business sustainability in the digital era.